THE IMPORTANCE OF USE ACTIVE LEARNING METHODS - Abdimominova, D.K.; Akhmetova, A.S. (PUBLISHINGS of Kostanay State Pedagogical University, 2019)
Problem of activity of the personality in training – one of actual in psychological, pedagogical science and educational practice. The task of the teacher consists in that not only to tell everything and to show clearly, but also to teach the pupil to think, impart to it skill of practical actions. It can be promoted by active forms and training methods. In work the problem of activity of the personality in training reveals, the characteristic of active methods of training is given, features of their use at a lesson are considered. In the article the necessity of the use of active methods of educating was considered for institution of higher learning. Howled the role of teacher and student is certain in an educational process.
Keywords: pedagogical innovation; interactive technologies of teaching; active teaching methods